Assessment of the Performance of Grinding Circuit for Buzwagi Gold Mine - Wikedzi, Alphonce (Tanzania Journal of Engineering and Technology, 2021)
It had been reported by the management of Buzwagi Gold Mine (BGM) that grinding circuit was designed to produce final product size of 125 Î¼m, which had not been achieved for a long period of time under both, low to normal (i.e. 450-600 t/h) and high (i.e. > 650 t/h) throughputs. Also, the performance behaviour of the circuit had not been reviewed after long time of operation. Hence, an evaluation study was conducted in order to recommend improvement in mine operations. The study was realized through three circuit survey campaigns and laboratory experimentations. From the surveys, size distributions and solids contents of the samples were determined for all selected circuit streams. Furthermore, grindability and work indices of the ores were determined through standard Bond tests. The standard Bond tests data revealed increased Bond work indices for currently treated ores vs. those during design, indicating change in ore hardness over the years. Consequently, a periodic review of the ore blends was recommended as harder material requires more energy, which increases operation costs. Such reviews could help in establishing better ore blending and optimum throughput for existing plant design. Furthermore, the SAG mill circuit indicated varying feed sizes (i.e. xF,80 =102 to 185 mm) which could be rectified by closer monitoring and control of ratios for the Semi-Autogenous Grinding (SAG) mill feeders drawing the ore from the stockpile. The ball mill performance was poor as indicated by only 5-9 % of < 125 µm (target product) in the discharge. This had a direct impact on hydrocyclones, where significantly poor performance indicators were observed; coarser overflow xP,80: >200 µm as well as cut size, xT: >200 µm. Also, the Bond efficiency factors in the range of 48-61 % were obtained, indicating an inefficient operation that could only achieve targets by lowering the current throughput. Hence, an optimization study of the existing design through computer modelling and simulation is recommended. Through simulation of multi-effects, a deeper understanding of the efficiency problems for the BGM grinding will be facilitated and also may provide possible solutions. Keywords: Comminution, Grinding circuit, SAG mill, Ball mill, Circuit survey, Bond work index, Bond efficiency factor, Gold ore blends.